2017
DOI: 10.46357/bcnaturais.v12i3.83
|View full text |Cite
|
Sign up to set email alerts
|

A A review of bioactive compounds produced by endophytic fungi associated with medicinal plants

Abstract: Interest in exploring endophytic fungi has increased in recent years, especially those associated with medicinal plants, reflecting the great potential of these microorganisms for the production of bioactive substances. Medicinal plants shelter a high diversity of endophytes that represent targets for use in biotechnological processes. These fungi synthetize several compounds that can be used in pharmaceutical, agricultural and other industries. Additionally, endophytes produce many bioactive metabolites invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…In the last years, due to studies on fungal biology, the importance of fungal SMs has been more widely recognized, and their pivotal participation in the survival, defense, and adaptation against biotic and abiotic conditions is well described. Over time, several different SMs were discovered, such as statins, cephalosporin (2) , and mycophenolic acid (3) , thus expanding and encouraging the studies for the discovery of more bioactive compounds by pharmaceuticals and agrochemicals companies [ 5 , 6 , 7 , 8 , 9 , 10 , 15 , 91 ].…”
Section: Bioactive Fungal Secondary Metabolites and Derivatives Succe...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the last years, due to studies on fungal biology, the importance of fungal SMs has been more widely recognized, and their pivotal participation in the survival, defense, and adaptation against biotic and abiotic conditions is well described. Over time, several different SMs were discovered, such as statins, cephalosporin (2) , and mycophenolic acid (3) , thus expanding and encouraging the studies for the discovery of more bioactive compounds by pharmaceuticals and agrochemicals companies [ 5 , 6 , 7 , 8 , 9 , 10 , 15 , 91 ].…”
Section: Bioactive Fungal Secondary Metabolites and Derivatives Succe...mentioning
confidence: 99%
“…In the last years, various fungal bioactive SMs have been described [ 5 , 6 , 7 , 8 , 9 , 10 , 125 ], such as paclitaxel. Paclitaxel was initially discovered from the medicinal plant Taxus brevifolia , and its cytotoxicity and apoptotic effect were studied in vitro on different cancer cell lines such as BT220 (breast), H116 (colon), Int407 (intestine), HL251 (lung), and HLK210 (leukemia) and MCF-7 (breast cancer).…”
Section: Studies Of Fungal Secondary Metabolites As Cytotoxic and Ant...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the long run, this association remains imprinted in the genetic makeup of both partners, who start to develop complementary genetic systems (Moricca & Ragazzi, 2008). Soares et al (2017) reported that during co-evolution, endophytic fungi gradually adapted to specific microenvironments, including the uptake of some plant DNA segments into its genomes, as well as the insertion its DNA into the host genome.…”
Section: Fungi and Their Host Specificitiesmentioning
confidence: 99%
“…Fungi are a major group of microorganisms that produce a broad array of compounds with novel structures and unique bioactivities. One type of fungi colonizes the intercellular and/or intracellular regions of healthy plant tissues at a particular time and has no interference with and causes no pathogenic symptoms to the host [ 3 ]. These endophytic microorganisms are an important but less-explored source for the discovery of structurally novel natural products in drug research.…”
Section: Introductionmentioning
confidence: 99%